Approach Between Literature and Politics: Spanish Civil War View From Max Aub’s The Magic Labyrinth - Anderson de la Torre, Maria Antonia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
During the Spanish Civil War, Max Aub was part of that collective of Republicans that fled the country escaping from death once Franco reached power. As a writer, Aub used all his energy to compile in a series of six novels -The Magic Labyrinth- as many events as possible that were connected to the three years prior to the beginning of the dictatorship. His goal was, mainly, to compile events, as a chronist. In these chronicles, a fundamental topic arises: the effects of war on the production, reception and preservation of art. Writers, painters, musicians find themselves, suddenly, between cross fire. It seems impossible not to take sides. At least that is what Aub does, and he explains the shift in his ars poetica in Historia de la Novela Española Contemporánea, where he distances himself from his former mentor, Ortega y Gasset. Thus, he abandons the path of the dehumanization of art and focuses more in a realist literature, that shows the artist in the middle of war.